The genetics of glioblastoma - Yan, Hai (Henry Stewart Talks, 2015)
Classifications of glioblastoma, Isocitrate dehydrogenase 1 mutation as the fundamental mutation in malignant glioma, The genetic mechanism of telomere maintenance in gliomas, Molecular subclassifcation of gliomas